A review of pediocins and pediocin-like bacteriocins (PLBs) - Minaz, Y. A.; Karagulleoglu, Z. Y.; Nehri, L. N.; Tekeli, C.; Oney, T. M.; Kilic, P.; Altuntas, E. Gunes (PLAPIQUI(UNS-CONICET), 2024)
Bacteriocins are widely used in the food industry due to their bio-preservative potential and antimicrobial properties. Despite the large number of identified LAB bacteriocins, nisin, and pediocin PA-1 are the only ones that have been thoroughly studies in food system application studies. Genetic engineering of pediocins is an interesting open research area that could lead to the development of pediocins with enhanced properties. The aim of this review is to explain the general molecular structure of pediocin and pediocin-like bacteriocins (PLBs) produced by Pediococcus spp. and compare their structural advantages. Another goal is to identify what changes can be made to the molecular structures of pediocins and PLBs. In doing so, we hope to shed light on the potential applications of pediocins and PLBs in the food industry.
Keywords: Class IIa bacteriocins; Mechanism of action; Molecular structure; Pediocin; Pediococcus spp; LACTIC-ACID BACTERIA; PEDIOCOCCUS-ACIDILACTICI; LISTERIA-MONOCYTOGENES; ANTIMICROBIAL ACTIVITY; ESCHERICHIA-COLI; DISULFIDE BOND; ESSENTIAL OILS; PURIFICATION; PENTOSACEUS; Engineering